Multiparticle correlation studies in pPb collisions root s(NN)=8.16 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2020)
The second- and third-order azimuthal anisotropy Fourier harmonics of charged particles produced in pPb collisions, at root s(NN) = 8.16 TeV, are studied over a wide range of event multiplicities. Multiparticle correlations are used to isolate global properties stemming from the collision overlap geometry. The second-order elliptic harmonic moment is obtained with high precision through four-, six-, and eight-particle correlations and, for the first time, the third-order triangular harmonic moment is studied using four-particle correlations. A sample of peripheral PbPb collisions at root s(NN) = 5.02 TeV that covers a similar range of event multiplicities as the pPb results is also analyzed. Model calculations of initial-state fluctuations in pPb and PbPb collisions can be directly compared to the high-precision experimental results. This work provides new insight into the fluctuation-driven origin of the v(3) coefficients in pPb and PbPb collisions, and into the dominating overall collision geometry in PbPb collisions at the earliest stages of heavy ion interactions.
Keywords: PB-PB COLLISIONS; SIDE ANGULAR-CORRELATIONS; PROTON-LEAD COLLISIONS; LONG-RANGE; NEAR-SIDE; TRANSVERSE-MOMENTUM; FLOW; COLLECTIVITY